"Flipped OR": a modified didactical concept for a surgical clerkship in Oral and Maxillofacial Surgery. Issue 10 (December 2020) - Bock, A.; Heitzer, M.; Lemos, M.; Peters, F.; Elvers, D.; Kniha, K.; Hölzle, F.; Modabber, A.
Abstract: The concept of the clerkship at the Department of Oral and Maxillofacial Surgery was modified into a modern and sustainable teaching model with a flipped classroom approach. The aim was to prove whether these changes increased the students' learning success. For the preparation of the clerkship, an e-learning module with 10 chapters was established. Students were supposed to access one chapter ahead of each day's seminar. A test to assess the gain in knowledge was undertaken before and after participation in the clerkship. An evaluation took place after the test. The results of the test after the clerkship were significantly higher than before (p < 0.0001). The evaluation showed that the students were highly satisfied with the course in general, and the e-learning module specifically. In particular, the surgical videos helped them to better understand the operative steps. The clerkship at the Department of Oral and Maxillofacial Surgery was modified into a sustainable blended learning concept with a flipped classroom approach. With these developments, the "flipped operating room" was shown to be effective in improving knowledge and competence among undergraduate dental students.